Reduced energetic particle transport models enable comprehensive time-dependent tokamak simulations. (21st August 2019) - Podestà, M.; Bardóczi, L.; Collins, C.S.; Gorelenkov, N.N.; Heidbrink, W.W.; Duarte, V.N.; Kramer, G.J.; Fredrickson, E.D.; Gorelenkova, M.; Kim, D.; Liu, D.; Poli, F.M.; et al.
Abstract: Time-dependent integrated simulations through codes such as TRANSP are becoming an indispensable tool for the interpretation of existing experiments and predictions of optimized scenarios. For many practical cases, quantitative simulations need to include the effect of plasma instabilities on the evolution of a tokamak discharge. An example is the degradation in energetic particle (EP) confinement induced by instabilities, which in turn affects important source terms for heating, non-inductive current, and momentum in a simulation. The reduced-physics kick model provides phase-space resolved transport probability matrices to TRANSP that are used to account for enhanced EP transport by instabilities in addition to neoclassical transport. The model has recovered the measured Alfvén eigenmode (AE) spectrum on NSTX, NSTX-U and DIII-D, and has reproduced details of phase-space resolved fast ion diagnostic data measured on DIII-D for EP-driven modes and tearing modes. In general, the kick model has proven the potential of phase-space resolved EP simulations to unravel details of EP transport for detailed theory/experiment comparison and for scenario planning based on optimization of neutral beam injection parameters. In this work, the extension of the kick model to low-frequency instabilities such as tearing modes and fishbones, in addition to AEs, is assessed. The goal is to enable TRANSP simulations that retain the main effects of multiple types of instabilities through a common framework. Results from the NSTX/NSTX-U and DIII-D tokamaks show that the extension to multi-mode scenarios can expand the range of applicability of the model for more reliable, quantitative integrated simulations.